(untitled) (México, D.F., México, 1988)
This manual presents a set of procedures for the economic analysis of on-farm experiments. It is intended for use by agricultural scientists as they develop recommendations for farmers form agronomic data
Keywords: Agriculture,Farm management; Economic aspects,Research,Methodology,Study and teaching